(3GdeYjGQ GdeYQH hGdLGeY GdeZQH aj aJGhi EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3jHOC HeSFdI ef GdhUGjG s
(3BNQgG (B:s
(3GfJgi GdLRA GdSGOS ef GdeYjGQ HMeO Gddg hdG Mhd hdG bhI EdG HGddg JYGdi hMSf Yhfg hJhajbg hdGMhd hdG bhI EdG HGddg GdYdj GdYXje s
(3GdfSNI HgG MhGTs
(3HBNQg agQSJ ddeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B517s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs